The influence of benzene on the composition, diversity and performance of the anodic bacterial community in glucose-fed microbial fuel cells - Tyszkiewicz, Natalia; Truu, Jaak; Młynarz, Piotr; Pasternak, Grzegorz (Frontiers in Microbiology, 2024)
Bioelectrochemical systems offer unique opportunities to remove recalcitrant environmental pollutants in a net positive energy process, although it remains challenging because of the toxic character of such compounds. In this study, microbial fuel cell (MFC) technology was applied to investigate the benzene degradation process for more than 160 days, where glucose was used as a cometabolite and control. We have applied an inoculation strategy that led to the development of 10 individual microbial communities. The electrochemical dynamics of MFC efficiency was observed, along with their 1 H-NMR metabolic fingerprints and analysis of the microbial community. The highest power density of 120 mW/m 2 was recorded in the final period of the experiment when benzene/glucose was used as fuel, which is the highest value reported in a benzene/co-substrate system. Metabolite analysis confirmed the full removal of benzene, while the dominance of fermentation products indicated the strong occurrence of non-electrogenic reactions. Based on 16S rRNA gene amplicon sequencing, bacterial community analysis revealed several petroleumdegrading microorganisms, electroactive species and biosurfactant producers. The dominant species were recognized as Citrobacter freundii and Arcobacter faecis, Strong, positive impact of the presence of benzene on the alpha diversity was recorded, underlining the high complexity of the bioelectrochemically supported degradation of petroleum compounds. This study reveals the importance of supporting the bioelectrochemical degradation process with auxiliary substrates and inoculation strategies that allow the communities to reach sufficient diversity to improve the power output and degradation efficiency in MFCs over previously known limits. This work, for the first time provides an outlook on syntrophic activity of biosurfactant producers and petroleum degraders towards the efficient removal and conversion of recalcitrant hydrophobic compounds into electricity in MFCs.